ANALISIS HUKUM SISTEM PEMUNGUTAN BEA PEROLEHAN HAK ATAS TANAH DAN BANGUNAN DI KABUPATEN AGAM - FITH RYANTO (PREMISE LAW JURNAL, 2019)
Dosen Pembimbing:1.  Prof. Dr. Budiman Ginting, SH, MHUm2.  Dr. Bastari, MM3.  Prof. Dr. Muhammad Yamin, SH, MS, CNLand and Building Right Transfer Tax (hereinafter referred to asBPHTB) is collected based on self assessment system pursuant toarticle 9 in the Government Regulations No. 55/2016 on GeneralProvisions and Procedures of Regional Tax Collection. The RegionalRegulation of Agam Regency No. 7/2011 on BPHTB and theRegulations of the Reagent of Agam No. 40/2017 on the procedures ofBPHTB has caused legal uncertainty of this tax collection system. Theresearch problems are how the provisions of the land and buildingright transfer tax collection system in regulated in Agam Regency,how about the legal certainty of how much the BPHTB in AgamRegency due to verification, and how the fulfillment of legal certaintyprinciples on the transfer of the rights over land and building in theLand and Building Right Transfer Tax of Agam Regency due toverification.Keywords : Tax, BPHTB, Tax Collection System, Land and Building Right Transfer Tax